Faktor-Faktor yang Berhubungan Dengan Keluhan Muskuloskeletal Disorders (MSDs) pada Pekerja Pengangkat Ikan di Usaha Dagang Mina Karya Karangasem - Ni Wayan Rusni; Ni Made Hegard Sukmawati; I Putu Ning Arya Dyana (Aesculapius Medical Journal, 2023)
MSDs complaints can reduce worker productivity, increase healthcare costs, slow performance, and miss work due to illness. This study aims to determine the factors associated with MSDs complaints at Usaha Dagang Mina Karya Karangasem. This is an observational analytic study with cross sectional design conducted in March-May 2022. Target population is fish carrier workers at Usaha Dagang Mina Karya Karangasem. Total sample was 30 people with total sampling. Independent variables are age, body composition, work posture, years of service, length of work, and workload while dependent variable is MSDs complaints. Data were collected with questionnaire to determine risk factors, a REBA questionnaire to determine work posture, and a Nordic Body Map questionnaire to determine musculoskeletal complaints. Data were analyzed using Spearman's test with SPSS application. Based on the results of the study, there was a strong relationship between workload and MSDs complaints (r=0.713; p<0.001) and a very strong relationship between work posture and MSDs complaints (r=0.926; p<0.001). No significant relationship was found between age, BMI, years of service, and length of work on MSDs complaints. Business owners should provide education about good work posture to reduce MSDs complaints to workers. The workload in one transport should also be reduced